The functions of code switching in an English language classroom - Eva Fachriyah (Studies in English Language and Education, 2017)
The aims of this research is to gain a deep understanding and to knowing  the use of code-switching that have done by students and lecturers in interaction when teaching learning in English class. Specifically or as sub-focus in this research was aimed to determine the functions for the use of code switching that is used by both  of the speaker and hearer that in this case the interaction between lecturer and students when learning takes place. This research was conducted at the campus of the State Islamic Institute "Sultan Maulana Hasanuddin Banten" at the Faculty of Education and Teaching in English department at the third semester. This study was a qualitative research by using ethnography of communication method. The techniques and procedures of data collection were used such as observation, recordings and transcripts, and interviews. Based on data analysis, the use of code switching in English classroom has got the result for functions of code switching in interaction when the learning take place. Key words: code switching, English learning, ethnography communication.